PENGARUH EKSPOR, IMPOR, DAN PENGELUARAN PEMERINTAH TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT DI INDONESIA - B2051131005, HASUDUNGAN FRANSISKUS (Jurnal Ekonomi Daerah (JEDA), 2019)
This study entitled The Effect of Government Export, Import and Expenditure Values on Economic Growth and Community Welfare in Indonesia "aims to find out and analyze the influence of net exports, government spending on economic growth in Indonesia. and community welfare in Indonesia.It is a type of explanatory descriptive research, the variables studied are net exports (export-import), government expenditure, economic growth and HDI in 34 provinces in Indonesia. Data is obtained from the Ministry of Trade and BPS. The analytical method used is path analysis with multiple regression, t test, F test, Sobel test.The results of the analysis in the first regression showed that net exports had a positive and significant impact on economic growth but had no significant effect on the HDI. Government expenditure has a positive and significant effect on economic growth and is also significant to the HDI. The results of 2nd regression show that net exports have no effect on the HDI, but government expenditure has a significant effect on the HDI. The result of testing the indirect effect (Sobel test) of net exports and government expenditure on the HDI shows insignificant results, meaning that economic growth is not an intervener variable between net exports and government expenditure on the HDI. Keywords: export, import, government expenditure, economic growth, human development index.DAFTAR PUSTAKAAkhirman (2011), Pengaruh PDB, Jumlah Penduduk, Nilai Ekspor, Investasi (Pma,Pmdn),Laju Inflasi Dan Tenagakerja Terhadap Pertumbuhan Ekonomi Provinsi Kepulauan Riau Tahun 2005-2010 (Universitas Maritim Raja Ali Haji)Balassa, Bela (1986), Policy Response to Exogeneous Shocks in Developing Countries. American Economics Review, Vol 76, No 2 May, pp.75-78.Balassa, Bela (1986), Policy Response to Exogeneous Shocks in Developing Countries. American, Economics Review, Vol 76, No 2 May, pp. 75-78.Boediono (2011), Ekonomi Makro, Seri Sinopsis, Pengantar Ilmu Ekonomi No. 2. Edisi ke dua puluh tiga, BPFE – Yogyakarta, Indonesia.Chalid, Nursiah (2009), Peranan Ekspor dalam Perekonomian IndonesiaJurusan Ilmu Ekonomi Universitas Riau Pekanbaru (tidak dipublikasikan)Ghozali, H. Imam (2009), Aplikasi Analisis Multivariate dengan Program SPSS, Edisi Ketiga, Badan Penerbit Universitas Diponegoro, Semarang.Hakim, Rahman (2012), Hubungan Ekspor, Impor Dan Produk Domestik Bruto (PDB) Sektor Keuangan Perbankan Indonesia Periode Tahun 2000-2011: Suatu Pendekatan dengan Model Analisis Vector Autoregression (VAR) Tesis, Fakultas Ilmu Sosial Dan Ilmu Politik Departemen Ilmu Administrasi Program Pascasarjana (tidak dipublikasikan)Irham (2003), Analisis Perkembangan Ekspor Dan Pengaruhnya Terhadap Pertumbuhan Ekonomi Indonesia, JURNAL EKONOMI & BISNIS NO. 1, Jilid 8, Tahun 2003Jai S. Mah (2006), Export Promotion and Economic Development (The Case of Korea), Journal of World Trade; Feb 2006; 40, 1; ABI/Inform Research pg. 153-166.Jung and Marshall (1985), The Process of Industrial Development and Alternative Development Strategies. Princeton, N,J.: Princeton University Press.Mankiw, N. Gregory (2006), Principles Of Economics. Pengantar Ekonomi Mikro. Penerbit Selemba Empat. Jakarta.Mariam (2010), Pengaruh Nilai Tukar Rupiah, Ekspor, Impor Dan Investasi Terhadap Pertumbuhan Ekonomi Di Indonesia Periode 2000:1 - 2009, Departemen Ilmu Ekonomi Program Studi Ekonomi Pembangunan Fakultas Ekonomi Dan Bisnis Universitas Airlangga Surabaya (tidak dipublikasikan.Nanga, muana (2005),  Makro Ekonomi : teori, masalah dan kebijakan. P.T. Raja Grafindo PersadaJakarta.Nopirin (1999),  Ekonomi Moneter. Yogyakarta, BPFE-Yogyakarta.Salvatori, Dominick (1997), Ekonomi Internasional, Edisi V, Alih bahasa Aris Munandar, Jakarta, Erlangga.Samuelson (2004), Economics. Eighteenth edition. New York: McGraw-Hill.Samuelson, Paul A dan William D. Nordhaus (1995),  Ilmu Makroekonomi. Edisi Tujuh Belas. Teijemaban. Jakarta: PT Media Global Edukasi.Sritua Arief (1993), Pemikiran Pembangunan dan Kebijaksanaan Ekonomi.Penerbit Lembaga Riset Pembangunan. JakartaSugiyono (2007), Metode Penelitian Bisnis, Alfabeta, Bandung.Sulaiman, Muna, et.al, (2006), An Analysis Of Export Performance And Economic Growth Of Malaysia Using Co-Integraton And Error Correction Models, International Islamic University Malaysia.Suliyanto (2006), Metode Riset Bisnis, ANDI Yogyakarta.Suliyanto (2011), Ekonometrika Teerapan Teori dan Aplikasi Dengan SPSS, Andi, Yogyakarta.Sutawijaya, Adrian (2007), Pengaruh Ekspor dan Investasi Terhadap Pertumbuhan Ekonomi Indonesia Tahun 1980-2006, Fakultas Ekonomi Universitas Terbuka Jakarta.Todaro, MP dan Stephen C. Smith (2011) Pembangunan ekonomi di Dunia Ketiga.  Edisi Kesebelas. Jakarta, Erlangga.